Fabrication of a micro-thermoelectric cooler for room temperature applications by template assisted electrodeposition - García, J.; Pérez, N.; Mohn, M.; Sieger, T.; Schlörb, H.; Reith, H.; Schierning, G.; Nielsch, Kornelius (THERMINIC 2016 - 22nd International Workshop on Thermal Investigations of ICs and Systems, 2016)
Solid state refrigeration is of great interest due to its potential application in electronic and optoelectronic systems. Nowadays, macroscopic thermoelectric coolers are part of such systems and their cooling performance and reliability are well proven. However, the feasibility of microstructuring such kind of devices by means of photolithographic techniques, opens the possibility of integration on a chip for better local thermal management. Together with previous facts, electrodeposition processes are well known to be low cost, highly scalable and compatible with lithographic techniques. In this work we report on the fabrication of BiTe-based Micro-Thermoelectric Coolers by means of a mixed process flow involving photolithography and electrodeposition techniques. Materials and geometry of the device have been chosen to optimise the cooling performance on an integrated photonic system.
CRIS-Team Scopus Importer:2023-03-20